CRIMINAL LIABILITY AND COMPULSORY IN INTERNATIONAL CRIMINAL JUSTICE: THE CASE OF TRANSNATIONAL CORPORATIONS - Liakopoulos, Dimitris (Revista Jurídica (FURB), 2018)
The present study aims to explore the relationship of criminal liability and compulsory in international criminal justice according the founding of international individual criminal responsibility in relation on the Transnational Corporations. There are few cases in which an International Criminal Court has used previous international jurisprudence to establish a crime of conduct in international customary law, and in any case the importance of international judgments can not be underestimated as a general interpretative tool. The offer of incriminating solution that serves as an extrema ratio for the criminal penalties that are imputable to multinational companies and which completes the sanctioning apparatus of international law is one of the solution offered and the result of a reconstruction that started mainly from the examples of national laws, but it should not be overlooked, that the penal responsibility of the multinational companies was expressly foreseen and regulated in the draft of the Statute of the International Criminal Court.